Answer:1)5x^2-11x
2) x^2-3x
Step-by-step explanation:
1)(f+g)(x)
f(x)=3x-7
g(x)= 2x-4
[(3x-7)+(2x-4)](x)
3x^2-7x+2x6^2-4x
=<u>5x^2-11x</u>
2) (f-g)(x)
[(3x-7)-(2x-4)](x)
(3x-7-2x+4)(x)
3x^2-7x-2x^2+4x
x^2-3x
Answer:
PLZ HELP
Step-by-step explanation:
Circle A is located at (6, 5) and has a radius of 4 units. What is the equation of a line that is tangent to circle A from point C (2, 8)?
x = 2
y = −0.75x + 9.5
y = 1.33x + 1.66
x = 8
Answer:
Its either answer B. or D. Sorry if I'm wrong and I hope this sorta helps.
For these questions to be true and the equation of the tangent to have an equal y to the equation of the parabola i guess there has to be a "c" and in that case integrate the equation of the tangent you will have a = 5 and b = -18 then you substitute in the equation of the parabola with the point you have you will find that "c" = 21 and so the equation of the parabola becomes y = 5x^2 - 18 x +21
Answer: 32x^7y^15
Step-by-step explanation:
(x)^2(2xy^3)^5
= x^2 * 32x^5y^15
= 32x^7y^15